Bell's palsy in a seven-month-old twin infant: a case report - Melo, Ádonis Pereira de; Albuquerque Neto, João Batista Siqueira de; Veloso, Maria Fernanda de Lima; Lopes, Rafaella de Lima; Alves, João Guilherme Bezerra (Brazilian Journal of Case Reports, 2024)
Idiopathic peripheral facial paralysis is a rare condition in the pediatric population under one year of age, characterized by paralysis of the structures innervated by the facial nerve. This report describes the first infant in Brazil to be diagnosed with this clinical condition. A 7-months-old twin infant presented with altered left oromotor control and a discrete incomplete closure of the left eyelid when blinking, although with normal tear production. Her primitive reflexes were present and the spontaneous movements of the four limbs were normal. An investigation for infectious etiology and a magnetic resonance imaging of the brain were performed and did not show any alterations. Thus, the diagnosis of Bell's palsy was assumed, and oral prednisone was prescribed for five days. The patient evolved with total resolution of the facial paralysis during the first two weeks after discharge. Most cases of peripheral facial paralysis in children are idiopathic, while the others are associated with infectious and/or traumatic etiologies. There are still no consistent data proving the benefit of the use of corticoid alone or in combination with antiviral drugs for the treatment of children under one year of age.